The Concept of Heavenly Mandate (Tiānmìng) through Lens of Ibn Khaldun’s Civilization Cycle Theory (Tasyri’ Al-Umran) - Ardi Tri Yuwono; Bó Chén (Sunan Kalijaga: International Journal of Islamic Civilization, 2025)
The concept of Heaven's Mandate (Tiānmìng) was a political ideology applied during the Chinese Dynasty era to legitimize the king's power. This concept relates to the theory put forward by Ibn Khaldun, namely the cycle of civilization (Tasyri' Al-Umran). This research aims to integrate historical, philosophical, and sociological perspectives to provide a deeper understanding of the dynamics of civilization through the lens of Tasyri' Al-Umran and Tiānmìng. The method used in this study is qualitative with a literature study approach. The Tiānmìng as the basis for the legitimacy of power in the Chinese tradition, turns out to have a striking similarity with the theory of 'asabiyyah (group solidarity) and the theory of Tasyri' Al-Umran. A great civilization usually arises from a society that has endured harsh conditions, poverty, and struggle. Aspirations to live a prosperous, trouble-free life, coupled with social solidarity, encourage them to work hard to achieve their goals. When this dream comes true, a new civilization is born. The emergence of this new civilization is often accompanied by the decline of other civilizations, which then await their turn to be conquered by the next social group.